Gálè at gósu para karing mal a patulunan - Cadiang, Crispin, Nacpil ([Angeles City] Center for Kapampangan Studies, Holy Angel University, 2012)
A compilation of traditional Kapampangan songs for All Saints Day which includes 60 original hymns that honor saints revered by the people of Pampanga.
Includes bibliographical references (page 186).
Keywords: All Saints' Day music -- Philippines -- Pampanga; Songs -- Philippines -- Pampanga; All Saints' Day -- Philippines -- Pampanga; Music -- Philippines -- Pampanga